South-Carolina. By His Excellency the Right Honourable Lord Charles-Greville Montagu ... A proclamation : Whereas the present General Assembly of this province, stood prorogued to Thursday the fifteenth day of June, instant; and whereas a sufficient number of members to make a House of Assemby have not met, in pursuance of the said prorogation ... the same is hereby accordingly prorogued to Monday the said 26th day of June ... Given under my hand ... at Charlestown, this 16th day of June, Anno Dom. 1769 (Printed by Robert Wells, 1769)
June 16, 1769 Proclamation by Governor Charles Montagu which prorogued the General Assembly until June 26th. This delay was a result of an insufficient number of members meeting when the Assembly was originally set to start.